Refleksi Manajemen dan Kepemimpinan Pendidikan Islam - Abdullah, Wawan; Syarifudin, Encep; Musihah, Eneng (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2023)
The purpose of writing as a descriptive description through deductive about the Definition, Scope of Management, and Leadership of Islamic Education. The qualitative research method was chosen in this paper because it is more commonly used by humanities, social, and religious academics. a focus on qualitative research methods, carried out through literature study. The stages of the research were carried out by collecting library sources, both primary and secondary. This study classified data based on research formulas. In the advanced stages, data processing and/or citation of references were carried out to be displayed as research findings, abstracted to obtain complete information, and interpreted to produce knowledge for drawing conclusions. As for the interpretation stage, an analysis or approach is used, for example, philosophical, theological, Sufistic, interpretation, syarah, and others. The management components and functions contained in the verses of the Koran, are Planning (At-Tahthiith), Organizing (At-Tandziim), Implementation (At-Tathbiq) and Evaluation (Al-Isyraf). The scope of educational management is management related to many parties and multidisciplinary knowledge. Namely, management of education and educational staff, student management, curriculum management, financing management, facility and infrastructure management, school management, principal management, and community relations management. In principle, leadership is a decision and is more the result of a process of changing character or internal transformation within a person. In Islam in determining the leader several principles that must be met are Amanah, Fair, Amr Ma'ruf Nahi Munkar and Shura.